2018
DOI: 10.1021/acs.jpcb.8b02773
|View full text |Cite
|
Sign up to set email alerts
|

Electric-Field Effects on Ionic Hydration: A Molecular Dynamics Study

Abstract: In this work, we report the electric-field effects on ionic hydration of Cl, Na, and Pb using molecular dynamics simulations. It is found that the effect of weak fields on ionic hydration can be neglected. Strong fields greatly disturb the water orientation in the hydration shells of ions, though ion coordination number remains almost unchanged. Under strong fields, the first hydration shell of ions is significantly weakened and the ion-water interaction energy is dramatically reduced; surprisingly, the second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 41 publications
2
25
0
Order By: Relevance
“…This small diameter difference may not be sufficient to allow the passage of the chloride ion surrounded by a hydrate shell. Under physiological conditions, this shell can be weakened by the negative membrane potential, which cannot be modeled in our MD simulations [57]. Although the protein structure was not constrained in an open conformation during our metadynamics simulation, the chloride ion visited both sides of the bottleneck region.…”
Section: Discussionmentioning
confidence: 96%
“…This small diameter difference may not be sufficient to allow the passage of the chloride ion surrounded by a hydrate shell. Under physiological conditions, this shell can be weakened by the negative membrane potential, which cannot be modeled in our MD simulations [57]. Although the protein structure was not constrained in an open conformation during our metadynamics simulation, the chloride ion visited both sides of the bottleneck region.…”
Section: Discussionmentioning
confidence: 96%
“…Under an appropriate electric field, the fast-migrating cations will partially dehydrate near the space-confined nanopore, facilitating the association of Mg 2+ /Li + with the fast-migrating Cl − in the opposite direction, and thus the degree of association of cation with Cl − increases. The work of He et al [26] also showed the ion hydration may be affected as the electric field is greater than 1.0 V nm −1 , especially for Cl − , which may facilitate ion association. Our results indicate that Mg 2+ ions form stable clusters with Cl − ions under a certain electric field while Li + ions are not easy to form stable clusters with Cl − ions, enabling Li + pass through COO − nanopores more easily under a certain electric field.…”
Section: Ion Association and Hydration Characteristics In Nanoporementioning
confidence: 98%
“…Similarly, compared with 0.2 V nm −1 , the inner (1st and 2nd) shells around Mg 2+ or Li + become more flexible and expanding under the electric fields of 0.6−1.0 V nm −1 (Figure 4e,f), which may be attributed to the fast transporting of ions and the dynamics of the hydrogen bonding network. [26] For 1.0 V nm −1 , the number of water molecules in the inner shell is relatively small. Since the dehydration is conducive to the association of Mg 2+ and Cl − , they are easier to form ion associated structures under the electric field of 1.0 V nm −1 compared with other electric fields.…”
Section: Ion Association and Hydration Characteristics In Nanoporementioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that the ion coordination number increased with the increase of the ionic radius, but the number of hydrated water molecules decreased. Furthermore, He et al reported that ion hydration can be affected by strong electric field. The water orientation in the hydration shell of ion would be disturbed under strong fields, though the ion coordination number remained almost unchanged.…”
Section: Properties Of Hydrated Ions Under Nano‐confinementmentioning
confidence: 99%